Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/molecules27206791
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Proliferative and Pro-Apoptotic Effects of Digested Aglianico Grape Pomace Extract in Human Colorectal Cancer Cells

Abstract: Grape pomace (GP)—the major by-product of winemaking processes—still contains bioactive molecules with known beneficial properties for human health, such as an antiradical scavenging activity or an antiproliferative activity of tumors. In vitro studies have demonstrated that GP polyphenols specifically influence colon cancer cell proliferation. In addition to previously published work, we tested the phenolic compounds of Aglianico GP following an in vitro simulated gastrointestinal digestion on colorectal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 49 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Once biotransformed in less complex compounds such as phenolic acids, the generated metabolites and bioactive molecules will modulate the gut microbiota [45,47,48], exerting an effect similar to prebiotics by favoring the growth of beneficial bacteria and inhibiting the growth of pathogenic ones [47,49]. Studies have shown that the antioxidant and antiinflammatory activities exerted by the polyphenols act against metabolic disorders such as cancer, obesity, and diabetes via modulation of the gut microbiota [24,48,[50][51][52]. There is evidence that metabolic alterations induced by a high-fat diet can also be attenuated by polyphenols intake via activation of PPARα and GLUT4 [53].…”
Section: Discussionmentioning
confidence: 99%
“…Once biotransformed in less complex compounds such as phenolic acids, the generated metabolites and bioactive molecules will modulate the gut microbiota [45,47,48], exerting an effect similar to prebiotics by favoring the growth of beneficial bacteria and inhibiting the growth of pathogenic ones [47,49]. Studies have shown that the antioxidant and antiinflammatory activities exerted by the polyphenols act against metabolic disorders such as cancer, obesity, and diabetes via modulation of the gut microbiota [24,48,[50][51][52]. There is evidence that metabolic alterations induced by a high-fat diet can also be attenuated by polyphenols intake via activation of PPARα and GLUT4 [53].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the key role of cancer therapy in identifying compounds that induce cell apoptosis and play a key role in eliminating mutated hyperproliferating cells from the system. Phenolic compounds, with their antiproliferative and antitumor activities, are involved in the proliferation, differentiation, and apoptosis of various cancer cells, including colon cancer [ 4 , 39 ]. Also very important in terms of chemoprevention by phenolic compounds is their differential effect on cancer cells but not on normal cells [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…A substantial upregulation of Bax, as well as the Bax/Bcl-2 ratio and caspase-3, was observed in both HT29 and SW480 cells. UHPLC-DAD analysis revealed that anthocyanins, phenolic acids, and flavonoids were the primary components responsible for the elevated (total phenolic content) TPC and antioxidant activity in the Aglianico GP digested extract [ 91 ]. In 2021, Zhang and his co-workers studied the combined effect of chrysin and apigenin by suppressing the activity of P38-MAPK/AKT pathway in colorectal cancer.…”
Section: Nutraceuticals In Various Diseasesmentioning
confidence: 99%